'Warning: allergic to penicillin': association between penicillin allergy status in 2.3 million NHS general practice electronic health records, antibiotic prescribing and health outcomes. (10th April 2019) - West, R M; Smith, C J; Pavitt, S H; Butler, C C; Howard, P; Bates, C; Savic, S; Wright, J M; Hewison, J; Sandoe, J A T
Abstract: Background: The prevalence of reported penicillin allergy (PenA) and the impact these records have on health outcomes in the UK general population are unknown. Without such data, justifying and planning enhanced allergy services is challenging. Objectives: To determine: (i) prevalence of PenA records; (ii) patient characteristics associated with PenA records; and (iii) impact of PenA records on antibiotic prescribing/health outcomes in primary care. Methods: We carried out cross-sectional/retrospective cohort studies using patient-level data from electronic health records. Cohort study: exact matching across confounders identified as affecting PenA records. Setting: English NHS general practices between 1 April 2013 and 31 March 2014. Participants: 2.3 million adult patients. Outcome measures: prevalence of PenA, antibiotic prescribing, mortality, MRSA infection/colonization and Clostridioides difficile infection. Results: PenA prevalence was 5.9% (IQR = 3.8%–8.2%). PenA records were more common in older people, females and those with a comorbidity, and were affected by GP practice. Antibiotic prescribing varied significantly: penicillins were prescribed less frequently in those with a PenA record [relative risk (RR)  = 0.15], and macrolides (RR = 4.03), tetracyclines (RR = 1.91) nitrofurantoin (RR = 1.09), trimethoprim (RR = 1.04), cephalosporins (RR = 2.05), quinolones (RR = 2.10), clindamycin (RR = 5.47) and total number of prescriptions were increased in patients with a PenA record. Risk of re-prescription of a new antibiotic class within 28 days (RR = 1.32), MRSA infection/colonization (RR = 1.90) and death during the year subsequent to 1 April 2013 (RR = 1.08) increased in those with PenA records. Conclusions: PenA records are common in the general population and associated with increased/altered antibiotic prescribing and worse health outcomes. We estimate that incorrect PenA records affect 2.7 million people in England. Establishing true PenA status (e.g. oral challenge testing) would allow more people to be prescribed first-line antibiotics, potentially improving health outcomes.